Melanoma central nervous system metastases: An update to approaches, challenges, and opportunities. (1st September 2022) - Karz, Alcida; Dimitrova, Maya; Kleffman, Kevin; Alvarez‐Breckenridge, Christopher; Atkins, Michael B.; Boire, Adrienne; Bosenberg, Marcus; Brastianos, Priscilla; Cahill, Daniel P.; Chen, Qing; Ferguson, Sherise; Forsyth, Peter; et al.
Abstract: Brain metastases are the most common brain malignancy. This review discusses the studies presented at the third annual meeting of the Melanoma Research Foundation in the context of other recent reports on the biology and treatment of melanoma brain metastases (MBM). Although symptomatic MBM patients were historically excluded from immunotherapy trials, efforts from clinicians and patient advocates have resulted in more inclusive and even dedicated clinical trials for MBM patients. The results of checkpoint inhibitor trials were discussed in conversation with current standards of care for MBM patients, including steroids, radiotherapy, and targeted therapy. Advances in the basic scientific understanding of MBM, including the role of astrocytes and metabolic adaptations to the brain microenvironment, are exposing new vulnerabilities which could be exploited for therapeutic purposes. Technical advances including single‐cell omics and multiplex imaging are expanding our understanding of the MBM ecosystem and its response to therapy. This unprecedented level of spatial and temporal resolution is expected to dramatically advance the field in the coming years and render novel treatment approaches that might improve MBM patient outcomes.